2018
DOI: 10.1016/j.kint.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

PiT-2, a type III sodium-dependent phosphate transporter, protects against vascular calcification in mice with chronic kidney disease fed a high-phosphate diet

Abstract: PiT-2, a type III sodium-dependent phosphate transporter, is a causative gene for the brain arteriolar calcification in people with familial basal ganglion calcification. Here we examined the effect of PiT-2 haploinsufficiency on vascular calcification in uremic mice using wild-type and global PiT-2 heterozygous knockout mice. PiT-2 haploinsufficiency enhanced the development of vascular calcification in mice with chronic kidney disease fed a high-phosphate diet. No differences were observed in the serum miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 52 publications
(71 reference statements)
1
31
0
Order By: Relevance
“…The pattern and localization of calcification detected in this study are consistent with that observed in previous studies using this uremic DBA/2 mouse model of arterial medial calcification 26,[43][44][45] ; that is, calcification was focally distributed and 'patchy'. In human specimens where larger calcified deposits have been observed, 'patchy' or focally distributed calcifications have also been detected 5,[46][47][48] .…”
Section: Discussionsupporting
confidence: 91%
“…The pattern and localization of calcification detected in this study are consistent with that observed in previous studies using this uremic DBA/2 mouse model of arterial medial calcification 26,[43][44][45] ; that is, calcification was focally distributed and 'patchy'. In human specimens where larger calcified deposits have been observed, 'patchy' or focally distributed calcifications have also been detected 5,[46][47][48] .…”
Section: Discussionsupporting
confidence: 91%
“…These two transporters were considered to play a redundant role in phosphate-induced osteoinduction in VSMCs [ 88 ]. However, the recent findings suggest that PIT2 may even protect against vascular calcification by the up-regulation of osteoprotegerin [ 89 ], a key regulator of bone metabolism and inhibitor of vascular calcification [ 31 , 90 ].…”
Section: Signaling Pathways Regulating Vsmcs Calcification During Higmentioning
confidence: 99%
“…Rodent models of CKD are used widely to study arterial medial calcification and include interventions such as vitamin D 3 overload, adenine administration, and 5/6 nephrectomy [ 14 , 15 , 16 ]. The calcification(s) observed in these models is often distributed focally and is ‘patchy’ in nature [ 17 , 18 ], which is similar to the patterns of calcification observed in specimens from patients with CKD [ 19 , 20 , 21 ]. Atherosclerotic apolipoprotein E knock-out (ApoE −/− ) and low-density lipoprotein receptor knock-out (LDLR −/− ) mice are popular models to study the development of arterial intimal calcification [ 22 ], with both micro- and macro-calcifications frequently detected in severe atheromatous plaques [ 23 , 24 ], as is the case in humans.…”
Section: Rodent Models Of Arterial Medial and Intimal Calcificatiomentioning
confidence: 83%